Optically induced nanostructures : biomedical and technical applications - König, Karsten; Ostendorf, Andreas (De Gruyter, 2015)
Nanostructuring of materials is a task at the heart of many modern disciplines in mechanical engineering, as well as optics, electronics, and the life sciences. This book includes an introduction to the relevant nonlinear optical processes as well as coverage of state-of-the-art applications of non-UV radiation such as cell reprogramming, surface treatments of implants, production of nanowires, friction modification, and 3D data storage.